MECHANIKAL JAUNDICE: PATHOMORPHO-LOGICAL CHARACTERISTICS OF THE LIVER IN EXPERIMENT - Борисенко В. Б.; Сорокіна І. В.; Горголь Н. І. (World of Medicine and Biology, 2014)
Experimental study on 36 Wistar rats, aimed to study histostructure changes of liver in mechanical jaundice. Using standard morphological and immunohistochemical techniques established that 14-day experiment on the background of significant intra - and extracellular cholestasis due to increased synthesis of interstitial collagens I and III types, and type IV collagen vascular membranes marked the beginning, and by 30 day complete formation of biliary cirrhosis.